Pengembangan metode skrining gizi untuk pasien dewasa rawat inap - Susetyowati Susetyowati; Hamam Hadi; Muhammad Hakimi; Ahmad Husein Asdie (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2012)
Background: A comprehensive nutrition assessment needs to be done on all hospitalized patients. The accuracy of nutritional assessment are necessary to ensure the provision of optimal nutrition support for the patient to prevent iatrogenic malnutrition and speed up the healing process. The nutrition screening tools has limited ability to be used as a valid indicator for comprehensive nutritional assessment. Thus, it is necessary to develop a new nutrition screening tool.Objective: To develop a simple, quick and valid malnutrition screening tool that can be used to identify adult patients at risk of malnutrition.Methods: This is an observational study with cross sectional design. The subjects were 495 patients admitted to Sardjito General Hospital, excluding paediatric, maternity, and psychiatric patients. All patients were screened using the Nutrition Screening Tool of University Gadjah Mada (NST-UGM). The validity of the NST-UGM will be tested by measuring the sensitivity and specifi city value compared to Subjective Global Assessment (SGA).Result: The newly developed nutrition screening tool consisted of 6 questions with a cut-off of 0-2 classifi ed as not at risk of malnutrition and > 2 classifi ed as at risk of malnutrition. The sensitivity and specifi city value of the new screening tool compared with SGA were 91.28 and 79.78 respectively. Therefore, the convergent and predictive validity of NSTUGM was established. Conclusion: The NST-UGM is a simple, quick and valid tool which can be used to identify patients at risk of malnutrition.